Mental health first aid training among healthcare French students: a qualitative study - Sibeoni, Jordan; Ellul, Pierre; Bubola, Théo; Debiche, Yanis; Piot, Marie-Aude (Frontiers in Medicine, 2023)
Background Healthcare students are a population more at risk for mental health issues, especially anxiety, depression, and suicidal thoughts. The health faculty of Université Paris Cité in France, Paris has implemented a Mental Health First Aid (MHFA) course aiming to improve students’ mental health literacy, self-care and peer-support and to decrease stigma about mental illness. We conducted a qualitative study exploring the lived experience of this MHFA training course among healthcare students so to better assess its implementation within this specific context and population. Methods This qualitative study used the five-stage inductive process to analyze the structure of lived experience (IPSE) approach. All the healthcare students that had completed the 2-day MHFA training were approached to participate. Data was collected through individual semi-structured interviews and inclusion continued until data saturation was reached. Data analysis was based on an inductive, descriptive, and structuring procedure to determine the structure of lived experience characterized by the central axes of experience. Results Twenty students were included. Data analysis produced a common structure of lived experience based on three central axes of experience, (1) a personal experience, (2) a student experience and (3) a professional experience. The participants all experienced this course intertwined within these 3 axes. Their motivation to take the course was personal -being of feeling concerned by the topic-, was study-oriented – to learn and revise psychiatry- and was professional – so to develop both practical and soft skills. In their personal experience, participants reported a transformative experience and some interventions with friends and family, while both in their student and professional experience, they felt frustrated with both the content and the form of the course. Conclusion The results reported similar outcomes reported in the literature about skills, knowledge, and awareness; but mostly produce original avenues about how to better adapt such course to this specific population so to better address students’ expectations and mental health issues. This MHFA course -with an adapted content addressing eating disorders, self-mutilations and sexual and gender-based violence – could be part of the early curriculum of healthcare students. The latter could then benefit from a level 2/advanced MHFA course years later specifically tailored for healthcare professionals.